2007
DOI: 10.1007/s11250-007-9099-9
|View full text |Cite
|
Sign up to set email alerts
|

Equine histoplasmosis: Treatment trial in cart horses in Central Ethiopia

Abstract: Therapeutic effects of Sodium Iodide (NaI), Potassium Iodide (KI), ground berries of "Endod" (Phytolacca dodecandra) and Penstrip were evaluated on 70 cases of equine hitoplasmosis (EH). Response to each treatment was assessed using clinical examination of the lesions. Statistically significant difference (P = 0.0036) in therapeutic effect was observed among the different remedies. Cases treated either with a combination of NaI and Penstrip (F = 6.34, P = 0.004) or "Endod" and Penstrip (F = 3.64, P = 0.031) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…Comparable results were reported with the aqueous extracts [6,7] . The present study showed that, n-butanol extract of P. dodecandra was effective against HCF.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Comparable results were reported with the aqueous extracts [6,7] . The present study showed that, n-butanol extract of P. dodecandra was effective against HCF.…”
Section: Discussionsupporting
confidence: 77%
“…The antifungal effect of the crude aqueous extract of P. dodecandra was demonstrated in vitro against different genera of dermatophytes of human pathogen and four clinical isolates of Candida albicans [5] . The crude aqueous extract was also found to have effect against HCF both in vitro and in vivo [6,7] . Further evaluation of different extracts of P. dodecandra on HCF isolates and cases of EL would of paramount importance towards the effort made to control EL in endemic countries.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of action is unknown, iodides are used as antifungal agents in horses due to their low cost and ease of administration (Carmalt et al 1999;Taintor et al 2004;Crothers et al 2009). Sodium iodide has been used successfully to treat many bacterial and fungal conditions in horses with a wide variety of dosing regimens employed (Baum et al 1984;Specht et al 1991;Chaffin et al 1992;Carmalt et al 1999;Davis et al 2000;Worster et al 2000;Lopez et al 2007;Hadush et al 2008;Crothers et al 2009). Besides sodium iodide, other systemic antifungal agents used in horses which could have been employed in Case 1 include the azoles (i.e.…”
mentioning
confidence: 99%
“…Healing of equine wounds particularly in the limbs is difficult due to hydrostatic factors and exposure to environmental contaminant which can lead to infection and delay healing (Tobianse et al, 2016). Bacillus, Aeromonus, Klebsiela, Staphylococcus, Micrococcus and Rhodococcus bacterial contaminants were reported in and on EL lesions (Hadush et al, 2008).…”
Section: Introductionmentioning
confidence: 98%